Dynamic Behavior of Sheet Pile in Sand under the Influence of Vibration - Noora J. Mousa; Waad A. Zakaria (Diyala Journal of Engineering Sciences, 2023)
This article includes an experimental investigation into the behavior of a vibratory force-exposed sheet pile set in sand. The study goal is to provide a parametric study. Regarding how vibrations affect the sheet pile's movement and rotation after layering the soil in a steel container with internal dimensions of 900 mm length, 400 mm wide and 400 mm high, a steel sheet pile with the dimensions of 350 mm length, 20 mm width and 0.5 mm thickness was inserted into the soil. The results showed that the speed, acceleration, and displacement increased with increasing the frequency of the vibration source when the source of vibration was situated at a distance of (D distance = H height of the sheet pile) and exposed to varied frequencies (5, 10, 15) Hz. As frequency is a type of energy, increased frequency will thus eventually cause more disturbance. The disturbance and its consequences on the soil will eventually increase as the frequency rises.